Oxidative Stress in Cataract Formation: Is There a Treatment Approach on the Horizon? - Jingyan Li; Francesco Buonfiglio; Ying Zeng; Norbert Pfeiffer; Adrian Gericke (MDPI AG, 2024)
Cataracts, a leading cause of blindness worldwide, are closely linked to oxidative stress-induced damage to lens epithelial cells (LECs). Key factors contributing to cataract formation include aging, arterial hypertension, and diabetes mellitus. Given the high global prevalence of cataracts, the burden of cataract-related visual impairment is substantial, highlighting the need for pharmacological strategies to supplement surgical interventions. Understanding the molecular pathways involved in oxidative stress during cataract development may offer valuable insights for designing novel therapeutic approaches. This review explores the role of oxidative stress in cataract formation, focusing on critical mechanisms, such as mitochondrial dysfunction, endoplasmic reticulum stress, loss of gap junctions, and various cell death pathways in LECs. Additionally, we discuss emerging therapeutic strategies and potential targeting options, including antioxidant-based treatments.